HUBUNGAN STRATEGI COPING DAN TINGKAT STRES TERHADAP SANTRI DI PONDOK PESANTREN DARUSSALAM KABUPATEN BANYUWANGI ( stady kasus asrama syafa’atul qur’an) - Agus Baihaqi; Titik Istiqomah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to determine and analyze the relationship between coping strategies and stress levels for students at the Darussalam Islamic boarding school, Banyuwangi district, the case stage in the Syafa'atul Qur'an dormitory. This research is a quantitative research using multiple correlation. The population of this study were all students of the Syafa'atul Qur'an dormitory, totaling 75 students, with a sample of 64 students. To measure the variables, the researcher used a questionnaire for the relationship between coping strategies (X1) and stress levels (X2) on students (Y). The results of this study indicate that coping strategies and stress levels are significantly related to students according to the analysis of the results of the multiple r correlation test which is 0.963. While the test results for the determinant F change <0.05 of 0.968 <0.005, which means that the dependent variable (coping strategy and stress level) is related to the independent variable (students). From this analysis, it can be concluded that accepting Ha and rejecting Ho, which means that there is a significant relationship between coping strategies and stress levels for students at the Darussalam Islamic boarding school, Banyuwangi district, in the case of the Syafa'atul Qur'an dormitory. Keywords: coping strategies, stress level, students